PENERAPAN MEDIA FLASHCARD UNTUK MENINGKATKAN KOSAKATA BAHASA INGGRIS SISWA KELAS 2 MADRASAH IBTIDAIYAH NEGERI 1 TANGERANG SELATAN - Widya Lestari; Fatma Nurmulia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This classroom action research aimed to improve the English vocabulary mastery of second-grade students at Madrasah Ibtidaiyah Negeri 1 Tangerang Selatan through the use of flashcards. The study was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The results indicated a significant improvement in students’ vocabulary mastery. In the pre-cycle, only 39% of students achieved the minimum passing grade. After the first cycle, the percentage increased to 50%, and in the second cycle, it reached 92%. The findings suggest that flashcards are effective learning media in enhancing students’ vocabulary acquisition and motivation. Flashcards also provided an enjoyable learning atmosphere, preventing boredom during English lessons.